2015
DOI: 10.1158/1078-0432.ccr-14-2648
|View full text |Cite|
|
Sign up to set email alerts
|

AXL Is a Logical Molecular Target in Head and Neck Squamous Cell Carcinoma

Abstract: Purpose Head and neck squamous cell carcinoma (HNSCC) represents the eighth most common malignancy worldwide. Standard of care treatments for HNSCC patients include surgery, radiation and chemotherapy. Additionally, the anti-epidermal growth factor receptor (EGFR) monoclonal antibody cetuximab is often used in combination with these treatment modalities. Despite clinical success with these therapeutics, HNSCC remains a difficult to treat malignancy. Thus, identification of new molecular targets is critical. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 55 publications
9
103
2
Order By: Relevance
“…In head and neck squamous cell cancer, Axl inhibition decreases cancer cell proliferation, migration and invasion, and increases sensitivity to the anti-EGFR antibody cetuximab. 25 In a breast cancer model, sensitivity to taxanes increased 1,000-fold with coincident Axl inhibition. 26 Axl is also expressed on endothelial cells and plays a role in angiogenesis.…”
Section: Role Of Axl In Cancermentioning
confidence: 99%
“…In head and neck squamous cell cancer, Axl inhibition decreases cancer cell proliferation, migration and invasion, and increases sensitivity to the anti-EGFR antibody cetuximab. 25 In a breast cancer model, sensitivity to taxanes increased 1,000-fold with coincident Axl inhibition. 26 Axl is also expressed on endothelial cells and plays a role in angiogenesis.…”
Section: Role Of Axl In Cancermentioning
confidence: 99%
“…Immunohistochemical analysis of primary tumors revealed that AXL expression correlates with metastasis and/or poor survival in patients with lung adenocarcinoma, glioblastoma multiforme, pancreatic, renal cell carcinoma, esophageal adenocarcinoma, oral squamous carcinoma, pleural mesothelioma, ovarian adenocarcinoma, colon cancer, head and neck squamous cell carcinoma, urothelial carcinoma, esophageal cell carcinoma, and hepatocellular carcinoma (Table 1, [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]). Moreover, AXL expression correlates with drug resistance in patients with melanoma, myeloid leukemia, lung cancer, and renal cell carcinoma [29,30,31,32,33,34].…”
Section: Gas6 and Axl Expression In Cancermentioning
confidence: 99%
“…AXL overexpression within chemoresistant tumors promotes survival through the activation of the AKT and ERK1/2 signaling pathways and decreases apoptosis through the modulation of c-ABL [71]. In addition to chemotherapy, AXL also promotes resistance to conventional radiotherapy in head and neck cancers [22]. …”
Section: Mechanisms Of Axl-mediated Tumor Progression and Metastasismentioning
confidence: 99%
“…Previous analysis indicated that UW-SCC1 was resistant to cetuximab therapy (24,25). Twelve mice were then injected with UWSCC-1 PDX in the flank and tumors were allowed grow to 200 mm 3 .…”
Section: Pan-her Treatment Leads To Decreased Tumor Growth In An Intrmentioning
confidence: 99%